Investment Behavior of Ugandan Smallholder Farmers: An Experimental Analysis - Hanna Julia Ihli; Oliver Mußhoff (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
In this study, we experimentally analyze the investment behavior of smallholder farmers in Uganda. We consider a problem of optimal stopping, stylizing an option to invest in a project. We ascertain whether, and to what extent, the real options approach and the classical investment theory can predict farmers' investment behaviors. We also examine differences in the investment behavior with respect to the presence of a price floor, which is often used to stimulate investments. Furthermore, we look at learning effects. Our results show that both theories do not exactly explain the observed investment behavior. However, our results suggest that real options models better predict the decision behavior of farmers than the classical investment theory. The presence of a price floor and learning from personal experience during the experiment do not significantly affect the investment behavior. However, we find that specific socio-demographic and socio-economic characteristics affect the investment behavior of farmers.
Keywords: C91; D03; D81; D92; 330; experimental economics; investment; price floors; real options; Uganda